The mystery of God : early Jewish mysticism and the New Testament - Rowland, Christopher, 1947- (Compendia Rerum Iudaicarum ad Novum Testamentum, 2009)
This book brings together the perspectives of apocalypticism and early Jewish mysticism to illuminate aspects of New Testament theology. The first part begins with a consideration of the mystical character of apocalypticism and then uses the Book of Revelation and the development of views about the heavenly mediator figure of Enoch to explore the importance of apocalypticism in the Gospels and Acts, the Pauline Letters and finally the key theological themes in the later books of the New Testament. The second and third parts explore the character of early Jewish mysticism by taking important themes in the early Jewish mystical texts such as the Temple and the Divine Body to demonstrate the relevance of this material to New Testament interpretation.